AI Readiness and Procurement Performance: The Mediating Role of E-Catalogue from Human Resource Capability Perspective in the Public Sector - Pangestuti, Dwi (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2026)
This study examines the effect of AI readiness conceptualized as a human resource driven organizational capability on procurement performance, with the mediating role of E-Catalogue Version 6.0 in the public sector. Data were collected from 63 procurement practitioners using a structured questionnaire with a five-point Likert scale and analyzed using PLS-SEM. The results show that AI readiness significantly affects procurement performance (β = 0.375, p = 0.002) and E-Catalogue implementation (β = 0.608, p < 0.001). In turn, E-Catalogue implementation significantly influences procurement performance (β = 0.425, p < 0.001). The indirect effect of AI readiness on procurement performance through E-Catalogue is also significant (β = 0.258, p = 0.002), indicating partial mediation. This study addresses the limited attention to human resource capability in prior e-procurement and digital transformation research. These findings highlight that procurement performance is not solely determined by digital systems but by the organization’s capability to develop and utilize human resources in AI-driven environments. This study contributes to the HRM literature by positioning AI readiness as an organizational capability rooted in human capital and digital competencies, extending its role in public sector digital transformation.